-9 divided by 27
13 answers
-9 divided by 27 is approximately -0.3333333333.
a-9 divided by 27 as a fraction
To write -9 divided by 27 as a fraction, you can put -9 as the numerator and 27 as the denominator.
So, -9 divided by 27 as a fraction is -9/27.
So, -9 divided by 27 as a fraction is -9/27.
simplified
To simplify -9/27, we can divide the numerator and denominator by their greatest common divisor, which is 9.
-9 ÷ 9 = -1
27 ÷ 9 = 3
So, -9/27 simplifies to -1/3.
-9 ÷ 9 = -1
27 ÷ 9 = 3
So, -9/27 simplifies to -1/3.
-11 divided my 4 as a mixed number
To express -11 divided by 4 as a mixed number, we can first perform the division.
-11 ÷ 4 = -2 remainder 1
The quotient is -2 and the remainder is 1. So, the mixed number is -2 1/4.
-11 ÷ 4 = -2 remainder 1
The quotient is -2 and the remainder is 1. So, the mixed number is -2 1/4.
11 divided my -4 as a mixed number
To express 11 divided by -4 as a mixed number, we can first perform the division.
11 ÷ -4 = -2 remainder 3
The quotient is -2 and the remainder is 3. So, the mixed number is -2 3/4.
11 ÷ -4 = -2 remainder 3
The quotient is -2 and the remainder is 3. So, the mixed number is -2 3/4.
-91 divided by -13 divided by 7
To solve the expression -91 divided by -13 divided by 7, we need to follow the order of operations, which is to perform the division from left to right.
First, we divide -91 by -13:
-91 ÷ -13 = 7
Next, we divide the result (7) by 7:
7 ÷ 7 = 1
So, -91 divided by -13 divided by 7 is equal to 1.
First, we divide -91 by -13:
-91 ÷ -13 = 7
Next, we divide the result (7) by 7:
7 ÷ 7 = 1
So, -91 divided by -13 divided by 7 is equal to 1.
72 divided by 4 divided by - 6
To solve the expression 72 divided by 4 divided by -6, we need to follow the order of operations, which is to perform the division from left to right.
First, we divide 72 by 4:
72 ÷ 4 = 18
Next, we divide the result (18) by -6:
18 ÷ -6 = -3
So, 72 divided by 4 divided by -6 is equal to -3.
First, we divide 72 by 4:
72 ÷ 4 = 18
Next, we divide the result (18) by -6:
18 ÷ -6 = -3
So, 72 divided by 4 divided by -6 is equal to -3.